2015
DOI: 10.3109/08820139.2015.1085389
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Regulate Secretion of IL-8 from Human Intestinal Epithelial Cell Linesin vitro

Abstract: Short-chain fatty acids (SCFAs) including acetate, propionate and butyrate play an important role in the physiological functions of epithelial cells and colonocytes, such as immune response regulation. Human intestinal epithelial cells (IECs) contribute in intestinal immune response via different ways, such as production of different immune factors including Interleukin (IL) IL-8, which act as chemoattractant for neutrophils, and subsequently enhance inflammation. Therefore, we aimed to evaluate the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 75 publications
2
30
1
Order By: Relevance
“…Iraporda et al 29 found that SCFAs (mainly, butyrate and propionate) reduce the expression of CXCL8 and CCL20 by Caco‐2 cells in vitro in response to flagellin stimulation, an effect that was not related to GPCRs activation. The inhibitory effect of the SCFAs on CXCL8, an important neutrophil chemoattractant, was also observed in other IECs cell lines and was associated with the inhibition of HDAC activity 30 …”
Section: Epithelial Cellsmentioning
confidence: 62%
See 3 more Smart Citations
“…Iraporda et al 29 found that SCFAs (mainly, butyrate and propionate) reduce the expression of CXCL8 and CCL20 by Caco‐2 cells in vitro in response to flagellin stimulation, an effect that was not related to GPCRs activation. The inhibitory effect of the SCFAs on CXCL8, an important neutrophil chemoattractant, was also observed in other IECs cell lines and was associated with the inhibition of HDAC activity 30 …”
Section: Epithelial Cellsmentioning
confidence: 62%
“…SCFAs interact with neutrophils and modulate their recruitment, effector function and survival at different tissues (reviewed in Rodrigues et al 33 ). These bacterial metabolites alter neutrophils recruitment by their ability to regulate the production of inflammatory mediators including cytokines that activate endothelial cells such as TNF‐α and IL‐17 and neutrophil‐chemoattractants such as CXCL1 and CXCL8 by different cells 26 , 28 , 29 , 30 , 34 , 35 . In addition, SCFAs activation of FFAR2 in neutrophils has been shown to induce their chemotaxis 7 , 36 , 37 …”
Section: Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Butyrate may also modify epithelial cell gene expression, for example IL-8 and monocyte chemoattractant protein 1, and this in turn would change the signaling of the epithelial cell to the mucosal immune system [15,16]. SCFA cause an altered lymphocyte numbers in the spleen and intestinal mucosa in addition to cytokine formation [17].…”
Section: Acidificationmentioning
confidence: 99%